RISK FACTORS FOR MORTALITY IN INTENSIVE CARE UNIT-ACQUIRED PNEUMONIA DUE TO KLEBSIELLA PNEUMONIAE - Sönmez, Ufuk; Çağlayan, Derya; Singil, Sarp; Ersan, Gürsel; Atalay, Sabri (Sanamed, 2023)
Objective: Hospital-acquired pneumonia (HAP) developing in intensive care units (ICU) is an important problem. Gram-negative bacteria are the most important cause of HAP. Among these bacteria, Klebsiella pneumoniae is among the most important pathogens. The mortality rate for infections caused by carbapenem-resistant Klebsiella pneumoniae is high. Identifying mortality risk factors is crucial to prevent potential deaths. The aim of this study was to determine the risk factors associated with mortality in HAP due to Klebsiella pneumoniae in intensive care unit patients.Material and Methods: This cross-sectional study was conducted between 01. May 2021. and 01. May 2023. in the Anesthesia and Reanimation Intensive Care Unit of Izmir Tepecik Training and Research Hospital. Patients aged 18 years who were diagnosed with hospital-acquired pneumonia due to Klebsiella pneumoniae were included in the study. The dependent variable of the study was 14-day mortality due to Klebsiella pneumoniae pneumonia. Independent variables were presence of COVID-19, bacteremia, ceftazidime/avibactam treatment, intubation, sepsis, Charlson comorbidity score, and laboratory parameters. We conducted logistic regression analysis using the backward elimination method to identify independent predictors of mortality.Results: A total of 176 patients were included in the study. The mean age of the patients was 64.6±16.2 years and 64.2% were male. The 14-day mortality rate was 29% (n:51). In the regression analysis performed to determine the risk factors for mortality; in the univariate regression analysis, day 0 leukocyte count > 10.600/mm3 (OR: 2.31; 95% CI: 1.10-4.84), platelet value < 140. 000/mm3 (OR: 2.26; 95% CI: 1.06-4.81), AST >50 U/L (OR: 2.40; 95% CI: 1.20-4.79) and creatinine >1.3 mg/dL (OR: 1.96; 95% CI: 1.006-3.82) were associated with mortality. In multivariate regression analysis, a leukocyte count >10.600/mm3 (OR: 2.30; 95% CI: 1.03-5.14) and an AST >50 U/L (OR: 2.23; 95% CI: 1.04-4.75) were found to be independent predictors of mortality.Conclusion: In conclusion, leukocytosis and high AST levels were found to be independent risk factors associated with mortality in cases of Klebsiella pneumoniae in the intensive care unit. Taking these factors into account, in addition to other parameters and scores that determine the prognosis of patients, may be useful in reducing mortality.
Keywords: Klebsiella pneumoniae; mortality; pneumonia; risk factors; intensive care units